Faktor-Faktor Penghambat Keterampilan Membaca Permulaan Pada Siswa Kelas II SD Negeri 1402 Hapung - Siti Adinda Hariyati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
If you think of it, education is like a light that illuminates the darkness, so that with this light humans are able to see the situations around them. The type of research carried out by the author is field, namely research that is directly related to the object being studied. The method used in this research is a qualitative descriptive method. The research carried out by the author is field research that is directly related to the object under study. Descriptive research is research that guides researchers to explore and photograph social situations in a comprehensive, broad and in-depth manner. The research subjects included class II students at SD Negeri 1402 Hapung, Ulu Sosa District, Padang Lawas Regency, while the objects of research were factors inhibiting initial reading skills in class II students at SD Negeri 1402 Hapung. Based on the results of observations, interviews, documentation results, from the findings of the discussion, the researcher concluded that the factors inhibiting the initial reading skills of class II students at SD Negeri 1402 Hapung had four factors, namely the first factor was the teacher, the second factor was the students, the third factor was the family or parents and the fourth factor is the learning process.